Application of modern simulation tools for the cyclic operation process of underground natural gas and carbon dioxide storage in an aquifer - Diakonchuk, S. A.; Stohniy, O. V.; Dubrov, D. P.; Nepapyshev, Ye. O.; Zhurman, B. D. (Oil and Gas Power Engineering, 2026)
The authors collected and analyzed geological-geophysical and technological information on the Chervonopartyzansky underground gas storage area. A brief overview of the main data on geological structure, history of creation, and features of storage operation is provided. Based on the collected geological-geophysical information, the authors created a 3D static geological model of the reservoir layers, which subsequently formed the basis for gas-hydrodynamic calculations. The general methodological principles and main stages of creating the gas-hydrodynamic model are highlighted. During the study, the mentioned methods were adapted taking into account the available factual data and applied in the creation and adaptation of the Chervonopartyzansky UGS gas-hydrodynamic model. Historical data on the operational modes of wells and the storage as a whole, volumes of injected and withdrawn gas, and reservoir pressure values were analyzed. The Chervonopartyzanske UGS was created in a water-bearing horizon of Bathonian age of the Middle Jurassic. Pilot-industrial exploitation began in 1968, and in 1985 the storage facility was brought to the design operating mode with 67 wells in use. Within the framework of this study, the authors reconstructed the period of exploitation from the beginning of the creation of the artificial reservoir in the aquifer up to 1981. Through iterative adaptation in the process of historical comparison of the period of creation and pilot-industrial exploitation of the UGS, the correspondence of calculated parameters to the real ones was achieved at a level of 90%. An alternative scenario of UGS operation in CO2 storage mode was modeled. According to the results, the range of reservoir pressure change and the gas-saturated pore space occupied by CO2 in the gaseous phase are 5-10% lower compared to natural gas, with all other parameters remaining unchanged. Based on the obtained results, an overview of production tasks and challenges that can be solved using a gas-hydrodynamic model of a gas storage facility, which meets the target parameters of detail and accuracy, is provided.